The quality assurance system at ENS Constantine: From principles to implementation - Boukredime, Fedoua; Idjet , Ahlem (Journal of Human Sciences, 2022)
In this article, we will present the self-assessment operation carried out by the École Normale Supérieure Assia Djebar de Constantine (ENSC) in the field of Quality Assurance and whose primary objective is to conduct an inventory of the establishment. The operation consists of an analysis of the various aspects of the organization and functioning of the school with the aim of establishing an action plan with a view to improving performance and guaranteeing maintenance and improvement of quality in the seven areas defined by the National Quality Assurance Reference System. We will present the progress of the operation, the various actors concerned, the difficulties encountered, the weaknesses and the strengths identified as well as the various recommendations.